Some Results on Chromatic Polynomials of Hypergraphs - Walter, Manfred (The Electronic Journal of Combinatorics, 2009)
In this paper, chromatic polynomials of (non-uniform) hypercycles, unicyclic hypergraphs, hypercacti and sunflower hypergraphs are presented. The formulae generalize known results for r-uniform hypergraphs due to Allagan, Borowiecki/Łazuka, Dohmen and Tomescu. Furthermore, it is shown that the class of (non-uniform) hypertrees with m edges, where m_r edges have size r, r≥ 2, is chromatically closed if and only if m≤4, m_2≥ m-1.